Traditionalism and modernity in conflict: a study on the organizational structure of Kampung Baru, Malaysia - Md Yassin, Khairil Azhar (Common Ground Publishing LLC, 2011)
Abstract: This paper attempts to find out the extent to which traditional values are taking into consideration in developing Kampung Baru. Kampung Baru was established as a Malay community by the British government since 1899. In order to administer the affairs and to look after the needs of Kampung Baru residents, the Administration Board of Malay Agricultural Settlement of Kampung Baru (M.A.S) was set up in 1900. Kuala Lumpur City Hall (KLCH/DBKL), however, after the inclusion of Kampung Baru in the Federal Territory of Kuala Lumpur in 1974, was also entrusted to manage and to develop the settlement. The main findings of this study indicate that to administer and to manage Kampung Baru is a complex task and should not be looked only from the organizational and development perspectives. Studies, especially by Western anthropologists and sociologists, have often emphasized the importance of organizational, management and development standpoints in analyzing the roles and functions of a particular organization. However, this study suggests that in the case of Kampung Baru, ethnic perspective, which is the maintenance of Malay identity and the needs to safeguard the Malay rights, should also be considered in developing the settlement.